PENGARUH RASIO PROFITABILITAS DAN RASIO SOLVABILITAS TERHADAP NILAI PERUSAHAAN YANG DIMODERASI OLEH AUDIT DELAY - Luh Gede Kusuma Dewi; Ni Luh Putu Sandrya Dewi; Nyoman Trisna Herawati (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2022)
This research aims to identify the effect of profitability ratio (Return on Assets-ROA) and solvency ratio (Debt to Equity Ratio-DER) on the value of a company, and to identify audit delay expertise in moderating the effect of ROA and DER on firm value. The population in this research is a variety of industries listed on the IDX in 2015-2019 totaling 44 listed on the IDX in 2015-2019. The data sampling used is a purposive side method. The dependent variable of this research is the value of the company as measured by Tobins'q. The independent variables of this research are return on assets and debt to equity ratio. The moderating variable for this research is audit delay. The research results show (a) ROA does not affect firm value, (b) DER affects firm value, (c) Audit delay strengthens ROA's effect on firm value, and (d) Audit delay weakens DER's effect on firm value.